Who Differentiates by Skin Color? Status Attributions and Skin Pigmentation in Chile - Torres, Fernanda; Salgado, Mauricio; Mackenna, Bernardo; Núñez, Javier (Frontiers in Psychology, 2019)
A growing body of research has shown that phenotypes and skin pigmentation play a fundamental role in stratification dynamics in Latin American countries. However, the relevance of skin color on status attribution for different status groups has been little studied in the region. This article seeks to broaden the research on phenotypic status cues using Chile as a context for analysis – a Latin American country with a narrow although continuous spectrum of skin tones, marked status differences, and a mostly white elite. We draw on status construction theory to hypothesize that skin pigmentation in Chile has become a status cue, although its heuristic relevance could differ across status groups. Using visual stimuli and a repeated measure design, we studied this relationship and tested whether the use of skin pigmentation as a status cue is conditional upon the status of those categorizing others. The results reveal that participants attribute, on average, lower status to others of darker skin. Besides, skin pigmentation has a conditional effect on the social status of participants: whereas skin pigmentation does not work as a status cue for lower status participants, it is an important status marker for the categorizations that middle and especially higher status participants perform. The phenotypic composition of reference groups of low and high-status individuals and system justification are discussed as potential explanations for these results.